Effective Interference Cancellation Scheme for Device-to-Device Communication Underlaying Cellular Networks - Shaoyi Xu; Haiming Wang; Tao Chen; Qing Huang; Tao Peng (2010 IEEE 72nd Vehicular Technology Conference - Fall, 2010)
It is expected that Device-to-Device (D2D) communication is allowed to underlay future cellular networks such as IMT-Advanced for spectrum efficiency. However, by reusing the uplink spectrums with the cellular system, the interference to D2D users has to be addressed to maximize the overall system performance. In this paper, a novel method to deal with the resource allocation and interference avoidance issues by utilizing the network peculiarity of a hybrid network to share the uplink resource is proposed and the implementation details are described in a real cellular system. Simulation results prove that satisfying performance can be achieved by using the proposed mechanism.